Making Singapore a major dispute resolution/arbitration centre in the maritime industry - Goh, Glendon Zi Wei (2012)
As part of Singapore’s efforts to promote itself as an international maritime centre, there is a need to provide a multitude of services for the maritime industry. Arbitration is a popular form of dispute resolution in the maritime industry. Therefore it is imperative that Singapore develops her maritime arbitration services, to cater to the needs of the community.